From anthropocentrism to sociology of things and digital sociology - S. Kibakin (Цифровая социология, 2019)
The genesis of socio-humanitarian and sociological knowledge, namely: understanding and studying the phenomenon of human life, its biological, vital, informational and social aspects has been revealed. The regularity of the transformation of anthropocentrism under the influence of the development of science and technology, the emergence of the concept of post-humanism has been substantiated. The examples of man-made disasters, the use of weapons of mass destruction, as social facts, that had a significant impact on the development of mankind, have been adduced. The conditions for the emergence of object-oriented sociology and the sociology of things have been shown, some scientific approaches have been disclosed within the framework of this concept of Graham Harman, Brun Latour and his followers. Separately, the methodological approaches of the actor-network theory have been disclosed, the main one has been highlighted. Separately, the methodological foundations of cognition of the world of things have been described within the framework of object-oriented sociology, related to the rejection of opposing pairs of the concepts “society and nature”, “truth is non-truth”, “structure and process” and others. The connection of this theory with the sociology of translation has been shown. The characteristic of the problems of development of the scientific and methodological base of digital sociology in the context of changing the content of social relations “man – machine” on the example of the information and communication network Internet has been given. Among them, have been allocated the problems of delegation to digital technologies, more and more powers in solving complex socio-technical problems, the global centralization of digital resources management, the emergence of virtual actors of social interaction. The author reduces specific examples of the use of actor-network theory to interpret the processes and phenomena of interaction between users of Internet resources with individual components of the Internet. Separately, promising areas of research in this area, related to the phenomena of the Internet of things and neuronet, have been highlighted.